The Influence of Talent Retention and Performance Management on Management Talent with Talent Development as a Moderating Variable in UPT PLN Padangsidimpuan Employees - M. Syahputra Siregar; Sri Rahayu; Hernawaty (CV. Doki Course and Training, 2026)
Talent management is a strategic issue for organizations, especially in the public sector, in maintaining the sustainability and competitiveness of human resources. This study aims to analyze the influence of talent retention and performance management on talent management with talent development as a moderating variable in UPT PLN Padangsidimpuan employees. This study uses a quantitative approach, where all 102 employees of UPT PLN Padangsidimpuan were used as respondents. Data was collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of the SmartPLS 4 application. The results of the study show that talent retention, performance management, and talent development have a positive and significant effect on talent management. Performance management is the most dominant variable influencing talent management. However, talent development is not able to moderate the influence of talent retention and performance management on talent management. The results of this study show that talent development plays a role as an independent variable, not as a moderating variable, in the research model